MOBILE APPLICATION BASED ON THE ANDROID PLATFORM TO IMPROVE INVENTORY MANAGEMENT IN THE PROPERTY CONTROL ADMINISTRATION DEPARTMENT - JIMENEZ, SANTIAGO LINDER RUBIÑOS (2024)
CURRENTLY IN THE DEPARTMENT OF ADMINISTRATION OF PATRIMONIAL CONTROL THE LACK OF USE OF TECHNOLOGIES TO PERFORM THE INVENTORY AND VERIFY THE REGISTERED MOVABLE GOODS IS VISUALIZED, REASON FOR WHICH CAN PRODUCE THE DISORDER OF THE INFORMATION AND ITS SUBSEQUENT LOSS. THEREFORE, THE OBJECTIVE OF THIS RESEARCH IS TO DEVELOP A MOBILE APPLICATION TO IMPROVE THE INVENTORY TAKING PROCESS. THIS IS WHY A GRAPHICAL INTERFACE WAS DEVELOPED THAT ALLOWS THE VERIFICATION AND REGISTRATION OF MOVABLE ASSETS, THIS INTERFACE IS BASED ON APP INVENTOR WHICH IS A VISUAL BLOCK ENVIRONMENT, CREATED FOR THE DEVELOPMENT OF MOBILE APPLICATIONS, WHICH RESULTED IN A 93.75% SATISFACTION RATE, 100% ACCURACY WHEN REQUESTING INFORMATION FROM THE FIREBASE AND A LATENCY OF 142.3 MS WHEN VERIFYING THE INFORMATION ADDITIONALLY, THE APP CAN WORK WELL ON DEVICES RUNNING ANDROID 7.0 AND ABOVE WITH A MAXIMUM PACKET LOSS OF 10.72%, WHICH ALLOWS CONCLUDING THAT THE MOBILE APPLICATION IS USABLE, CORRECTLY VERIFIES A MOVABLE ASSET AND THE APPLICATION CAN PERFORM REMOTE MONITORING ON A CONSTANT BASIS. © 2024 LATIN AMERICAN AND CARIBBEAN CONSORTIUM OF ENGINEERING INSTITUTIONS. ALL RIGHTS RESERVED.